2017
DOI: 10.1002/stem.2704
|View full text |Cite|
|
Sign up to set email alerts
|

Runt-Related Transcription Factor 2 Induction During Differentiation of Wharton’s Jelly Mesenchymal Stem Cells to Osteoblasts Is Regulated by Jumonji AT-Rich Interactive Domain 1B Histone Demethylase

Abstract: Novel bone regeneration approaches aim to obtain immature osteoblasts from somatic stem cells. Umbilical cord Wharton's jelly mesenchymal stem cells (WJ-MSCs) are an ideal source for cell therapy. Hence, the study of mechanisms involved in WJ-MSC osteoblastic differentiation is crucial to exploit their developmental capacity. Here, we have assessed epigenetic control of the Runt-related transcription factor 2 (RUNX2) osteogenic master regulator gene in WJ-MSC. We present evidence indicating that modulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…Maintenance of chromatin with low H3K4me3 enrichment (and hence elevated H3K4me1) at the Runx2 promoter can be also achieved by binding and activity of the H3K4 demethylase Jarid1b/Kdm5b (Figure 1; Rojas et al, 2015Rojas et al, , 2019Bustos et al, 2017;Sepulveda et al, 2017a), which converts H3K4me3 to H3K4me1 (Christensen et al, 2007;Iwase et al, 2007;Yamane et al, 2007). Targeted depletion of Jarid1b/Kdm5b in mice results in elevated lethality at early post-natal stages, exhibiting these animals cranial dysmorphic parameters and skeletal alterations (Albert et al, 2013).…”
Section: Methylation At Histone H3k4 and H3k27 Residuesmentioning
confidence: 99%
“…Maintenance of chromatin with low H3K4me3 enrichment (and hence elevated H3K4me1) at the Runx2 promoter can be also achieved by binding and activity of the H3K4 demethylase Jarid1b/Kdm5b (Figure 1; Rojas et al, 2015Rojas et al, , 2019Bustos et al, 2017;Sepulveda et al, 2017a), which converts H3K4me3 to H3K4me1 (Christensen et al, 2007;Iwase et al, 2007;Yamane et al, 2007). Targeted depletion of Jarid1b/Kdm5b in mice results in elevated lethality at early post-natal stages, exhibiting these animals cranial dysmorphic parameters and skeletal alterations (Albert et al, 2013).…”
Section: Methylation At Histone H3k4 and H3k27 Residuesmentioning
confidence: 99%
“…Among the multiple factors that are known to affect epigenetic state, histone modifications have been identified as a process that is vital to the fate decision of MSCs [7][8][9]. Histone modifications affect gene expression via changes in the configuration of chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…Current study by Bustos and colleagues have demonstrated that JARID1B (Jumonji AT-rich interactive domain 1B) histone demethylase represses Runx2 in undifferentiated WJ-MSCs. In JARID1B knockdown murine, it can be seen that Runx2 is highly expressed and ready for osteogenic commitment indicating that this molecular mechanism is relevant to modulating osteoblastic lineage commitment [ 63 ].…”
Section: Introductionmentioning
confidence: 99%